Neoantigens in cancer immunotherapy: focusing on alternative splicing - Huang, Peng; Wen, Feng; Tuerhong, Nuerye; Yang, Yang; Li, Qiu (Frontiers in Immunology, 2024)
Alternative splicing (AS) functions as a crucial program in transcriptional modulation, leading to proteomic diversity and functional alterations of proteins. These splicing actions induce various neoantigens that hold prognostic significance and contribute to various aspects of cancer progression, including immune responses against cancer. The advent of immunotherapy has remarkably revolutionized tumor therapy. In this regard, AS-derived neoantigens are potent targets for cancer vaccines and chimeric antigen receptor (CAR) T cell therapies. In this review, we outline that ASderived neoantigens serve as promising immunotherapeutic targets and guide immunotherapy strategies. This evidence contributes to a deeper comprehension of the complexity of proteomic diversity and provides novel perspectives and techniques for precision medicine in immunotherapy.Moreover, we underscore the obstacles that are awaited to be addressed for this novel approach to become clinically applicable.